Transfer printing film and preparation method thereof
By using the transfer film prepared by using cycloolefin resin and buffer layer material, the problem of easy curling and high cost of polytetrafluoroethylene film is solved, and the quality stability and production efficiency of fuel cell cells are improved.
Patent Information
- Application Number
- CN202411638045.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-16
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polytetrafluoroethylene films are easily curled when carrying the catalyst layer, resulting in unstable quality of fuel cell cells and high cost, with uneven thickness and turning printing problems, affecting industrial production.
The thermal transfer resin made of cycloolefin resin, syndiotactic polystyrene resin and poly-4-methyl-1-pentene resin are used as the transfer layer, and the buffer layer of polyurethane or polyolefin material is combined with PET and PEN The transfer film is prepared by solvent coating to ensure layer uniformity and adhesion.
The thickness consistency and surface flatness of the transfer film are achieved, the transfer effect of the catalyst layer and the yield of the hot-press transfer process are improved, the cost is reduced, and the quality stability and production efficiency of the fuel cell are ensured.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a transfer film and a preparation method thereof. Background Art
[0002] As a new type of clean energy, fuel cells (Proton Exchange Membrane Fuel Cells, PEMFC) have attracted widespread attention due to their low pollution or even pollution-free nature. The core component of PEMFC, membrane electrode assembly (MEA), provides a continuous channel for protons, electrons, reaction gases and water for the electrochemical reaction of PEMFC, and is the focus of researchers, especially the research on its manufacturing process. The transfer method is to coat, print or spray the pre-prepared catalyst slurry onto a certain transfer medium, i.e., a transfer membrane, and then transfer the catalyst layer to the proton exchange membrane after drying to obtain a proton exchange membrane (Catalyst Coated Membrane, CCM) covered with a catalyst layer. Since the transfer method has removed the solvent before transfer, the proton exchange membrane will not swell, and the catalyst layer has a strong binding force with the proton exchange membrane. Therefore, the transfer method is considered to be a reliable method suitable for industrial continuous production of membrane electrodes.
[0003] In the existing process of preparing membrane electrode by flat-plate hot pressing transfer, polytetrafluoroethylene film (PTFE) is used as the transfer membrane. Although PTFE film has a certain bearing effect when used as a transfer membrane and can be easily peeled off after hot pressing with the proton exchange membrane, the PEFE film itself is relatively soft and is very easy to curl after heating the catalyst layer, resulting in poor hot pressing composite with the proton membrane; at the same time, the PTFE membrane is produced by a turning process, resulting in poor thickness uniformity of the PTFE membrane itself and a turning printing problem. When spraying or scraping the catalyst layer, it is easy to cause uneven thickness of the catalyst layer, resulting in different thicknesses of the catalyst layer transferred to both sides of the proton exchange membrane, affecting the unstable quality of the fuel cell cell; in addition, the transfer membrane as an engineering component for carrying the catalyst layer is a disposable product, with a large amount and low yield, but the PTFE membrane itself is expensive, resulting in a significant increase in cost.
[0004] In summary, PTFE membrane has great disadvantages and shortcomings as a transfer membrane in the fuel cell manufacturing process. The market urgently needs a material that can replace PTFE film for roll-to-roll membrane electrode CCM continuous thermal transfer. Summary of the invention
[0005] The first technical problem to be solved by the present invention is: to provide a transfer film with low cost and good quality of fuel cell obtained after transfer in view of the shortcomings of the prior art.
[0006] To solve the above-mentioned first technical problem, the technical solution of the present invention is: A transfer film comprises a transfer layer, a buffer layer and a support layer; The transfer layer is a thermal transfer resin prepared by a solvent coating method using any one of cycloolefin resin, syndiotactic polystyrene resin and poly-4-methyl-1-pentene resin; The buffer layer is composed of polyurethane or polyolefin material; The support layer is one of PET, PEN, PI, PPS, PEI, and PPSU film materials.
[0007] Preferably, the thermal transfer resin is an amorphous cyclic polyolefin resin.
[0008] Preferably, the transfer layer has a thickness of 0.5-5 μm.
[0009] Preferably, the buffer layer has a thickness of 10-30 μm.
[0010] Preferably, the support layer has a thickness of 50-150 μm.
[0011] The second technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a method for preparing a transfer film is provided, which has low cost and good quality of the fuel cell obtained after transfer.
[0012] To solve the above second technical problem, the technical solution of the present invention is: A method for preparing a transfer film comprises the following steps: S01. Preparation of buffer layer resin Adding polyurethane or polyolefin elastomer particles and organic solvent I into a reaction kettle, stirring and dissolving completely at 50-70°C, and then filtering to obtain a buffer layer resin; S02. Preparation of buffer layer The buffer layer resin prepared in S01 is filtered through a 200-800 mesh filter or a 1-20 um filter element, coated on the substrate layer by a scraper, CED or anilox roller coating device, and rolled up after being completely dried; S03. Preparation of thermal transfer resin Add any one of cycloolefin resin, syndiotactic polystyrene resin, poly-4-methyl-1-pentene resin and organic solvent II into a reaction kettle, stir and dissolve completely at 70-90° C., and then filter to obtain a silicon-free thermal transfer resin; S04, transfer membrane preparation The silicone-free thermal transfer resin prepared in S03 is filtered through a 200-800 mesh filter or a 1-20 um filter element, coated on the substrate layer with a buffer layer prepared in S02 through an anilox roller coating device, and rolled up after being completely dried to obtain a transfer film product.
[0013] Preferably, the organic solvent I and the organic solvent II are any one of butanone, N,N-dimethylformamide, cyclohexane, xylene or toluene, or a mixed solution of two or more thereof.
[0014] Preferably, the mass ratio of the polyurethane or polyolefin elastomer particles to the organic solvent I is 100:150-500.
[0015] Preferably, the mass ratio of the cycloolefin resin, the syndiotactic polystyrene resin or the poly-4-methyl-1-pentene resin to the organic solvent II is 100:400-1900.
[0016] Preferably, the stirring speeds in steps S01 and S03 are both 300-900 r / min.
[0017] Due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The transfer film prepared by the present invention has good thickness consistency and low surface roughness, can achieve a complete transfer effect for catalyst materials of different formulations, and has a simple production process and low cost.
[0018] 2. The transfer film prepared by the present invention has excellent temperature resistance and a small shrinkage rate during the thermal transfer process, thereby effectively improving the yield of the hot pressing transfer process.
[0019] 3. The transfer film material and the polyurethane or polyolefin buffer layer material prepared by the present invention can not only effectively buffer the pressure during the thermal transfer process but also improve the adhesion between the thermal transfer layer and the support layer.
[0020] 4. The transfer film material prepared by the present invention, the transfer layer of cycloolefin resin, syndiotactic polystyrene resin and poly-4-methyl-1-pentene resin not only has excellent catalyst transfer effect, but also the molecular structure of the thermal transfer resin is stable, without silicon elements or other substances that affect the activity of the catalyst, which can ensure that the thermal transfer process will not transfer or release substances that affect the activity of the catalyst, thereby improving the stability of the quality of CCM products.
[0021] 5. The transfer membrane material prepared by the present invention is low in price and has superior performance. It improves the yield and efficiency in the CCM process to varying degrees, achieving the purpose of reducing costs and increasing efficiency of fuel cells. The transfer membrane is easy to recycle or process without any environmental problems. DETAILED DESCRIPTION
[0022] The present invention will be further described below in conjunction with the embodiments. Example 1
[0023] A method for preparing a transfer film comprises the following steps: S01. Preparation of buffer layer resin Add E685 polyurethane produced by Yantai Meirui and butanone in a weight ratio of 1:150 into a reactor, stir at 60°C and 300 r / min for 60 min, and filter after complete dissolution to obtain a buffer layer resin; S02. Preparation of buffer layer The buffer layer resin prepared in S01 was filtered through a 200-mesh filter, coated on the 10 μm to 50 μm PET substrate layer by a doctor blade coating device, and rolled up after being completely dried; S03. Preparation of thermal transfer resin The cycloolefin resin 6017S of Japan Polyplastics and toluene were added into the reactor at a weight ratio of 100:400, stirred at 70°C and 300 r / min for 30 min, and filtered after complete dissolution to obtain the silicone-free thermal transfer resin; S04, transfer membrane preparation The silicone-free thermal transfer resin prepared in S03 was filtered through a 200-mesh filter, and coated with 1 μm on the substrate layer with a buffer layer prepared in S02 through an anilox roller coating device. After being completely dried, it was rolled up to obtain a transfer film product. Example 2
[0024] A method for preparing a transfer film comprises the following steps: S01. Preparation of buffer layer resin Add E695 polyurethane produced by Yantai Meirui and N,N-dimethylformamide into a reactor at a weight ratio of 1:350, stir at 60°C and 500r / min for 100min, and filter after complete dissolution to obtain a buffer layer resin; S02. Preparation of buffer layer The buffer layer resin prepared in S01 was filtered through a 10 μm filter element, coated on a 15 μm to 50 μm PEN substrate layer through a doctor blade coating device, and rolled up after being completely dried; S03. Preparation of thermal transfer resin The syndiotactic polystyrene resin C142 produced by Idemitsu Kosan of Japan and cyclohexane were added into the reaction kettle at a mass ratio of 100:800, stirred at 80°C and 600 r / min until completely dissolved, and then filtered to obtain the silicone-free thermal transfer resin; S04, transfer membrane preparation The silicone-free thermal transfer resin prepared in S03 was filtered through a 400-mesh filter, and coated with 2 μm on the substrate layer with a buffer layer prepared in S02 through an anilox roller coating device. After being completely dried, it was rolled up to obtain a transfer film product. Example 3
[0025] A method for preparing a transfer film comprises the following steps: S01. Preparation of buffer layer resin A mixed solution of Toyobo polyolefin PKA-KH resin, cyclohexane and xylene in a weight ratio of 100:500 was added into a reactor, stirred at 70°C and 900 r / min for 60 min, and filtered after complete dissolution to obtain a buffer layer resin, wherein the weight ratio of cyclohexane to xylene was 1:1; S02. Preparation of buffer layer The buffer layer resin prepared in S01 was filtered through a 1 μm filter element, coated with 30 μm on a 50 μm PI substrate layer by a doctor blade coating device, and rolled up after being completely dried; S03. Preparation of thermal transfer resin A mixed solution of Japanese Mitsui poly-4-methyl-1-pentene resin MX002, butanone and xylene was added into a reaction kettle at a mass ratio of 100:1900, stirred at 90°C and 900 r / min for 60 minutes, and filtered after complete dissolution to obtain a silicone-free thermal transfer resin; S04, transfer membrane preparation The silicone-free thermal transfer resin prepared by S03 was filtered through a 5μm winding filter element, and coated on the substrate layer with a buffer layer prepared by S02 with a thickness of 5μm by an anilox roller coating device. After being completely dried, it was rolled up to obtain a transfer film product. Example 4
[0026] A method for preparing a transfer film comprises the following steps: S01. Preparation of buffer layer resin A mixed solution of Toyobo polyolefin PKA-KH resin, butanone, N,N-dimethylformamide and cyclohexane in a weight ratio of 100:400 was added into a reactor, stirred at 60°C and 400 r / min for 120 min, and filtered after complete dissolution to obtain a buffer layer resin, wherein the weight ratio of butanone, N,N-dimethylformamide and cyclohexane was 1:2:1; S02. Preparation of buffer layer The buffer layer resin prepared in S01 was filtered through a 20 μm filter element, coated with 10 μm on a 100 μm PPSU substrate layer through a doctor blade coating device, and rolled up after being completely dried; S03. Preparation of thermal transfer resin The cycloolefin resin 6017S of Polyplastics of Japan and xylene were added into the reactor in a weight ratio of 100:800, stirred at 80°C and 700r / min for 30min, and filtered after complete dissolution to obtain the silicone-free thermal transfer resin; S04, transfer membrane preparation The silicone-free thermal transfer resin prepared in S03 was filtered through a 600-mesh filter, coated on the substrate layer with a buffer layer prepared in S02 with a thickness of 0.5 μm by an anilox roller coating device, and rolled up after being completely dried to obtain a transfer film product. Example 5
[0027] A method for preparing a transfer film comprises the following steps: S01. Preparation of buffer layer resin Add E685 polyurethane resin from Yantai Meirui and xylene in a weight ratio of 100:500 into a reactor, stir at 65°C and 600r / min for 120min, and filter after complete dissolution to obtain a buffer layer resin; S02. Preparation of buffer layer The buffer layer resin prepared in S01 was filtered through a 15 μm filter element, coated with 10 μm on a 150 μm PEI substrate layer by a doctor blade coating device, and rolled up after being completely dried; S03. Preparation of thermal transfer resin A mixed solution of Japanese Polyplastics' cycloolefin resin 6014S and N,N-dimethylformamide, xylene and toluene in a weight ratio of 100:1200 was added into a reactor, stirred at 80°C and 700 r / min for 30 min, and filtered after complete dissolution to obtain a silicone-free thermal transfer resin, wherein the weight ratio of N,N-dimethylformamide, xylene and toluene was 1:1:1; S04, transfer membrane preparation The silicone-free thermal transfer resin prepared in S03 was filtered through an 800-mesh filter, and coated on the substrate layer with a buffer layer prepared in S02 with a thickness of 3 μm by an anilox roller coating device. After being completely dried, the transfer film product was obtained by winding the resin. Comparative Example 1
[0028] The buffer layer resin and buffer layer preparation were omitted, and the rest was the same as in Example 2, and the transfer layer resin was directly coated on the surface of the PEN material. Comparative Example 2
[0029] Commercially available Kosai CSFM-1 oriented 100um PTFE membrane.
[0030] The performance of the products of the above-mentioned embodiments 1-5 and the products of comparative examples 1-2 were tested respectively. The specific test items and test methods are shown in Table 1 below, and the test results are shown in Table 2.
[0031] Table 1
[0032] Table 2
[0033] The test results show that the surface of the product composed of cycloolefin, buffer layer resin and support layer is uniform without shrinkage or cracks when the catalyst slurry is sprayed or directly coated. After the catalyst layer is completely dried, the transfer material has no warping or curling problems. After thermal transfer, the transfer is sufficient and there is no residue. The surface of the prepared catalyst layer is highly flat and has no texture problems.
[0034] It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.
Claims
1. A transfer film, Features: It includes a transfer layer, a buffer layer and a support layer; The transfer layer is a thermal transfer resin prepared by a solvent coating method using any one of cycloolefin resin, syndiotactic polystyrene resin and poly-4-methyl-1-pentene resin; The buffer layer is composed of polyurethane or polyolefin material; The support layer is one of PET, PEN, PI, PPS, PEI, and PPSU film materials.
2. A transfer film as claimed in claim 1, Features: The thermal transfer resin is an amorphous cyclic polyolefin resin.
3. A transfer film as claimed in claim 1, Features: The transfer layer has a thickness of 0.5-5 μm.
4. A transfer film as claimed in claim 1, Features: The buffer layer has a thickness of 10-30 μm.
5. A transfer film as claimed in claim 1, Features: The support layer has a thickness of 50-150 μm.
6. The method for preparing the transfer film according to any one of claims 1 to 5, It is characterized in that The following steps are involved: S01. Preparation of buffer layer resin Adding polyurethane or polyolefin elastomer particles and organic solvent I into a reaction kettle, stirring and dissolving completely at 50-70°C, and then filtering to obtain a buffer layer resin; S02. Preparation of buffer layer The buffer layer resin prepared in S01 is filtered through a 200-800 mesh filter or a 1-20 um filter element, coated on the substrate layer by a scraper, CED or anilox roller coating device, and rolled up after being completely dried; S03. Preparation of thermal transfer resin Add any one of cycloolefin resin, syndiotactic polystyrene resin, poly-4-methyl-1-pentene resin and organic solvent II into a reaction kettle, stir and dissolve completely at 70-90° C., and then filter to obtain a silicon-free thermal transfer resin; S04, transfer membrane preparation The silicone-free thermal transfer resin prepared in S03 is filtered through a 200-800 mesh filter or a 1-20 um filter element, coated on the substrate layer with a buffer layer prepared in S02 through an anilox roller coating device, and rolled up after being completely dried to obtain a transfer film product.
7. A method for preparing a transfer film according to claim 6, Features: The organic solvent I and the organic solvent II are any one of butanone, N,N-dimethylformamide, cyclohexane, xylene or toluene, or a mixed solution of two or more thereof.
8. A method for preparing a transfer film according to claim 6, Features: The mass ratio of the polyurethane or polyolefin elastomer particles to the organic solvent I is 100:150-500.
9. A method for preparing a transfer film according to claim 6, Features: The mass ratio of the cycloolefin resin, the syndiotactic polystyrene resin or the poly-4-methyl-1-pentene resin to the organic solvent II is 100:400-1900.
10. A method for preparing a transfer film according to claim 6, Features: The stirring speed in steps S01 and S03 is 300-900 r / min.
Citation Information
Patent Citations
Laminate and method for producing same
CN102438829A
Laminated film, method for manufacturing same, and method for manufacturing fuel cell
CN115803193A
Release film, laminate thereof, and method for producing film electrode assembly
CN118510658A
Laminated film
JP2009102558A
Laminated film, method for producing the same, laminated body, and method for producing catalyst layer-electrolyte membrane composite
JP2017081011A
Cited By
PO composite transfer printing film for out-of-mold transfer printing and preparation method of PO composite transfer printing film
CN120792277A
Viscosity-reduced PO composite transfer film and preparation method thereof
CN121004819A
